PENGUASAAN KOMPETENSI KRIYA KERAMIK PASCA PELATIHAN DALAM TINJAUAN FASET PEMAHAMAN WIGGINS DAN TIGHE - Rohmat Sulistya (SENDIKRAF Jurnal Pendidikan Seni dan Industri Kreatif, 2023)
Teachers attain a higher level of competency after participating in training. However, due to the short duration of training, not all aspects of competence are fully mastered by teachers. An effective strategy is needed to complement the lacking aspects of competence. This study aims to provide an overview of the mastery of competencies among teachers specializing in ceramic craft after training and how the concept of understanding according to Wiggins and Tighe is used to map the aspects of competencies that should be learned to achieve complete mastery. The research method involves reviewing journal references and books, supported by objective observations of several participating teachers.The results indicate that the mastery of competencies (both hard and soft skills) during training serves as a solid foundation, which can then be supplemented with self-directed learning strategies using the self-determined learning approach as a logical choice in the learning process. To facilitate the in-depth understanding of specific competency aspects, a mapping of competency aspects is proposed using the 6 (six) facets of understanding according to Wiggins and Tighe. This approach is alternative, allowing teachers to determine which facets to focus on based on their interests, characteristics, and academic arguments. Keywords: competency mastery, ceramic craft, post-training, understanding, Wiggins and Tighe ABSTRAK Guru memiliki level kompetensi yang lebih tinggi pascapelatihan yang diikuti. Tetapi dengan durasi pelatihan yang pendek, tidak seluruh aspek kompetensi dikuasai secara utuh oleh guru. Diperlukan strategi yang efektif untuk melengkapi aspek-aspek kompetensi yang kurang. Kajian ini bertujuan memberikan gambaran penguasaan kompetensi guru konsentrasi keahlian kriya keramik pascapelatihan dan bagaimana konsep pemahaman (understandings) menurut Wiggins dan Tighe digunakan untuk memetakan aspek-aspek kompetensi yang sebaiknya dipelajari agar diperoleh penguasaan kompetensi utuh. Metode kajian menggunakan telusur referensi jurnal dan buku diperkuat dengan pengamatan objektif kepada beberapa guru peserta pelatihan. Hasil kajian menunjukkan penguasaan kompetensi (hardskill dan softskill) selama diklat menjadi bekal yang baik untuk kemudian dilengkapi dengan strategi belajar mandiri sesuai pendekatan pembelajaran self-determined learning sebagai pilihan logis dalam belajar. Untuk memudahkan aspek-aspek kompetensi yang perlu diperdalam, diajukan pemetaan aspek kompetensi untuk dikuasai dengan pendekatan 6 (enam) faset pemahaman menurut Wiggins dan Tighe. Pendekatan ini bersifat alternatif, guru dapat menetapkan faset-faset mana yang dipilih sesuai kepentingan, karakter, dan argumentasi akademisnya. Kata kunci: penguasaan kompetensi, kriya keramik, pascapelatihan, pemahaman, Wiggins dan Tighe